การสร้างสรรค์ภาพผู้สูงอายุด้วยปูนซีเมนต์ฉาบสี ในรูปแบบเอกซเพรสชันนิสซึม จากชีวิตและผลงานของบุคคลสำคัญ (EXPRESSIONISM PAINTINGS OF FAMOUS PEOPLE’S ELDER LIFE BY COLOR CEMENT CREATION) - ทิมวัฒนบรรเทิง สาธิต (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2019)
ผู้วิจัยมีจุดมุ่งหมายเพื่อศึกษาการดำเนินชีวิตของผู้ที่มีผลต่อบริบททางสังคม เศรษฐกิจและการเมือง เพื่อสร้างสรรค์ผลงานศิลปะที่เกี่ยวกับผู้สูงอายุด้วยปูนซีเมนต์ฉาบสีในรูปแบบเอกซเพรสชันนิสซึม วิเคราะห์ด้วยการใช้เกณฑ์ 1. แนวความคิดในการสร้างผลงาน 2. หลักการทางศิลปะ การจัดวางองค์ประกอบภาพ รูปทรง พื้นผิว รูป พื้น และสี ผู้วิจัยพบว่าผู้สูงอายุที่อยู่ในสถาบันฯ จากผลงานในภาพ “พระบาทสมเด็จพระปรมินทรมหาภูมิพลอดุลยเดชฯ” พระบรมราโชวาทความว่า “เศรษฐกิจพอเพียง เป็นเสมือนรากฐานของชีวิต รากฐานความมั่นคงของแผ่นดิน เปรียบเสมือนเสาเข็มที่ถูกตอกรองรับบ้านตัวอาคารไว้นั่นเอง สิ่งก่อสร้างจะมั่นคงได้ก็อยู่ที่เสาเข็ม แต่คนส่วนมากมองไม่เห็นเสาเข็ม และเสาเข็มก็ลึกเสียด้วยซ้ำ” ผู้สูงอายุที่เคยเป็นนายกรัฐมนตรี ในภาพ “ฯพณฯ พลเอกเปรม ติณสูลานนท์” ซึ่งได้แสดงออกถึงความซื่อสัตย์และความจงรักภักดี ตัวแทนผู้สูงอายุ จากบุคคลสำคัญที่เป็นชาวต่างประเทศในภาพ “มหาตมะ คานธี” กล่าวไว้ว่า “จิตวิญญาณแห่งอหิงสาย่อมน้อมนำไปสู่ความอ่อนน้อมถ่อมตน” และในภาพตัวแทนผู้สูงอายุในสังคมยุคปัจจุบัน ที่สังคมควรได้ตระหนักในคุณค่าของผู้สูงอายุที่จะสามารถสร้างคุณประโยชน์ให้แก่สังคมได้ ตามความรู้และความสามารถ คำสำคัญ: ผู้สูงวัย ปูนซีเมนต์ฉาบสี เทคนิคการตกแต่ง The researcher aims to study the elder’s roles in social, economic and political contexts, to create expressionism art by using color cements decoration to reflect their roles, and touse color cement decoration as a medium to promote good relationship between the elder and society. The following criteria were employed in the study to inspire the researcher in creating the artworks: According to the study and the artworks, the elder presented in the royal institution of the researcher’s creative painting, ‘His Majesty King BhumibolAdulyadej’ is in accordance withthe royal guidance on “Sufficiency Economy” that “acts as a principle of life and a cornerstone of the nation, just like thefoundation piles that support houses and buildings. It is the foundation piles that secure the buildings. Yet, most people do not see them, and they are laid deeply underground. ”The painting of “His Excellency General PremTinsulanonda” represents an elder who was once the prime minister. This painting also reflects honesty and loyalty attributes of the elder. The painting of “Mahatma Ghandhi,”an influential foreign elder who once said “the spirit of nonviolence would lead to humbleness.” The last painting, “The Elder at Present” reflects the awareness of valuing old people who can contribute to society according to their knowledge and ability. Keywords: Elder Painting, Color Cement, Decoration Technique